Improving students’ problem-solving ability through STEM integrated project-based learning with formative assessment on thermodynamics topics - Syifa’ul Hasanah, Syifa’ul Hasanah (2023)
Thermodynamics consists of heat and work interrelated in the process of energy transfer. This material is one of the abstract physics materials so it is difficult for students to understand. This difficulty affects students when they find problems. Meanwhile, the treatment of project-based learning (PjBL)-STEM with formative assessment (FA) to build students' Problem Solving Abilities (PSA) is still rarely implemented. The purpose of this study was to increase students' PSA through PjBL-STEM with FA on thermodynamic topics. This study used a pre-and post-test design on 33 students of class XI MIPA SMAN in Gresik. Students make a simple engineering prototype in the form of a thermos and a steam engine. The research instrument is the thermodynamic problem-solving ability test instrument. The instrument test uses 5 essay questions with Cronbach's Alpha reliability of 0.922 (very high category). Research data were analyzed using paired t-test, N-gain, and d-effect size. The results showed that PjBL-STEM with FA had a significant impact on students' PSA, complemented by an increase in N-gain=0.34 (medium category) and d-effect size=3.4 (strong category). Before the application of the learning model, students had a low PSA, but after the application of the learning model, students were able to have a high PSA. However, after learning students still have difficulties in choosing the appropriate principle to the problem so that the overall mathematical procedure used and the solution given is not appropriate. It can be concluded that students' problem-solving abilities increased significantly from pretest to posttest in the medium category and the impact of implementation in the strong category after students were applied through PjBL-STEM with FA on thermodynamic topics. In future research, it is recommended to add "Art"and "Religious"aspects so that it becomes a STREAM approach in learning.